The Influence of Digital Marketing, Store Atmosphere, and Product Variation on Purchase Decisions at Warung Mina Dalung - Putu Krisnanda Aryasa PUTRA; I.B. Udayana PUTRA; Dewa Ayu Putu Niti WIDARI (Loka: Journal Of Environmental Sciences, 2024)
Purpose:The development of tourism in Bali has changed consumer consumption patterns, triggering intense competition in the accommodation, restaurant, and cafe industry. This requires businesses to innovate their marketing strategies to win. This study aims to evaluate the impact of digital marketing, store atmosphere, and product variety on purchasing decisions, using a case study of Warung Mina Dalung.Methodology:The sampling technique used was accidental sampling with 96 respondents and multiple linear regression analysis. Data were collected through observation, interviews, questionnaires, and literature review, and analyzed using validity and reliability tests and multiple linear regression analysis using SPSS.Findings:The findings show that all three tested variables significantly influence purchasing decisions, both simultaneously and partially. The three observed factors explain 26.9%, while other factors influence 73.1%.Implication:Multiple linear regression analysis shows that digital marketing, store atmosphere, and product variety significantly influence purchasing decisions, with a positive influence at Warung Mina Dalung.